A Theoretical and Experimental Investigation of the Spectroscopic Properties of a DNA‐Intercalator Salphen‐Type ZnII Complex. Issue 24 (14th May 2014) - Biancardi, Alessandro; Burgalassi, Azzurra; Terenzi, Alessio; Spinello, Angelo; Barone, Giampaolo; Biver, Tarita; Mennucci, Benedetta
Abstract The photophysical and DNA‐binding properties of the cationic zinc(II) complex of 5‐triethylammonium methyl salicylidene ortho‐phenylenediiminato (ZnL2+) were investigated by a combination of experimental and theoretical methods. DFT calculations were performed on both the ground and the first excited states of ZnL2+ and on its possible mono‐ and dioxidation products, both in vacuo and in selected solvents mimicked by the polarizable continuum model. Comparison of the calculated absorption and fluorescence transitions with the corresponding experimental data led to the conclusion that visible light induces a two‐electron photooxidation process located on the phenylenediiminato ligand. Kinetic measurements, performed by monitoring absorbance changes over time in several solvents, are in agreement with a slow unimolecular photooxidation process, which is faster in water and slower in less polar solvents. Moreover, structural details of ZnL–DNA binding were obtained by DFT calculations on the intercalation complexes between ZnL and the d(ApT)2 and d(GpC)2 dinucleoside monophosphate duplexes. Two main complementary binding interactions are proposed: 1) intercalation of the central phenyl ring of the ligand between the stacked DNA base pairs; 2) external electrostatic attraction between the negatively charged phosphate groups and the two cationic triethylammonium groups of the Schiff‐base ligand. Such suggestions are supported by fluorescence titrations performed on the ZnL/DNA system at different ionic strengths and temperatures. In particular, the values of the DNA‐binding constants obtained at different temperatures provided the enthalpic and entropic contributions to the binding and confirmed that two competitive mechanisms, namely, intercalation and external interaction, are involved. The two mechanisms are coexistent at room temperature under physiological conditions.